Evaluation of Maternal Dietary n-3 LCPUFA Supplementation as a Primary Strategy to Reduce Offspring Obesity: Lessons From the INFAT Trial and Implications for Future Research - Meyer, Dorothy Marie; Brei, Christina; Bader, Bernhard Lorenz; Hauner, Hans (Frontiers in Nutrition, 2020)
Preclinical research suggests that early exposure to LCPUFAs impacts offspring health outcomes, although evidence in humans is rather unclear. In 2006, we established the Impact of Nutritional Fatty acids during pregnancy and lactation on early human Adipose Tissue development (INFAT) study, a prospective randomized controlled intervention trial that examined whether decreasing the n-6/n-3 LCPUFA ratio during pregnancy and lactation influences offspring adipose tissue development in children up to 5 years. Our results indicate that maternal supplementation with n-3 LCPUFAs does not reduce offspring obesity risk, which is in line with recent publications. This perspective describes the challenges and lessons learned from our clinical trial. We discuss key findings and critically evaluate differences in study design, methodology, and analyses across similar intervention trials that may partly explain heterogenous results. Summarizing evidence from human trials, we conclude that n-3 LCPUFA supplementation should not be recommended as a primordial strategy to prevent childhood obesity. Instead, if remains open whether n-3 LCPUFA supplementation could benefit high-risk subgroups and some vulnerable maternal/child populations. The perspectives offered herein are derived largely from insights gained from ours and similar n-3 LCPUFA intervention trials and help to provide direction for future research that examines the impact of maternal nutritional exposure on offspring health and disease outcomes.